Effectiviness of Smartwatch Alarm Detector and PMR-Isometric Exercise as Hypertension Treatment - Bagus Ananta Tanujiarso; Natalia Nadia Azalia Dyah Wibowo; Risa Nadia Indraswari; Samuel Frandito Pramaditya T; Yoel Kristian Adi Candra (GLOBAL HEALTH SCIENCE GROUP, 2023)
Hypertension is the leading cause of death in the 21st century when systolic and diastolic blood pressure increases. Prevention of complications due to hypertension can be done by monitoring blood pressure. Smartwatch innovations are helpful in the health sector for monitoring blood pressure, which can be used as an initial screening for people. In addition to monitoring blood pressure, nonpharmacological therapy is one of the management of hypertension. A combination of progressive muscle relaxation and isometric exercise in hypertensive patients can help lower blood pressure by relaxing muscles. Objective: This research aims to determine the effectiveness of smartwatches in generating hypertension alarms and the effectiveness of pmr-isometric as therapy in lowering blood pressure. This research used a quick experiment with one group pre-post test design. The respondents were recruited by purposive sampling method for 16 hypertensive people. The inclusion criteria in this study are respondents aged 35-65 years, have good hemodynamic status to be able to do therapeutic exercises, can speak Indonesian, and do not have vision and hearing problems. Exclusion criteria were respondents who had advanced complications of hypertension, such as heart disease, stroke, paralysis, and immobilization. The intervention was given once for 20 minutes using a YouTube video connected to smartwatch and a demonstration followed by the respondent. The pre-test value was measured from the respondent's blood pressure 5 minutes before the intervention, while the post-test value was taken after 5 minutes. Data were analyzed by paired sample t-test. The results showed that the smartwatch alarm detector could detect blood pressure, and there was an effect of applying a combination of progressive muscle relaxation and isometric exercise on the blood pressure values of hypertensive patients with a p-value of 0.002 (p < 0.05). Smartwatch has proven effective as an early screening for hypertension and a combination of progressive muscle relaxation and isometric exercise, which effectively lower blood pressure in people with hypertension.